Analysis of Digital Infrastructure Development for the Indonesian Capital Market - Lisnawati Lisnawati; Muhammad Ikhsan Harahap (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Digital developments in the Indonesian capital market are influenced by regulatory policies and innovations carried out on an ongoing basis by Exchange Members (AB). In responding to the development of the digital economy, the government must be able to create policies such as ease of financing for startups, tax incentives, and fostering mastery of information and communication technology (ICT) for SMEs. The government also needs to develop telecommunications infrastructure and develop ICT education. Community participation to improve education and skills in the field of ICT also needs to be done in order to take advantage of existing opportunities for their welfare. So to succeed (survive) in this dynamic world, companies should not only perform traditional actions such as lowering costs, but also undertake activities such as changing innovation structures or processes as critical response activities. Most of the response activities could be better facilitated by Information technology.